Analysis of the Influence of Organizational Culture on Employee Performance Through Job Satisfaction (Study on DP3AKB Pasuruan City) - Nugroho, Agung Bagus; Triatmanto, Boge; Setiadi, M.Ch.Sina (Formosa Journal of Multidisciplinary Research, 2024)
This study used a saturated sampling or census technique to examine job satisfaction as a mediating influence of organizational culture on employee performance at the Office of Women's Empowerment, Child Protection and Family Planning (DP3AKB) in Pasuruan City. Path analysis (Path Analysis) is a data analysis approach. According to the study's findings, employee performance and job satisfaction are positively correlated with organizational culture, with job satisfaction acting as a mediating factor in this relationship. The leadership of Pasuruan City's Office of Women's Empowerment, Child Protection, and Family Planning (DP3AKB) must follow scientific and technological advancements and pay attention to employee satisfaction in order to establish a positive organizational culture and increase employee performance. Workers must be highly driven in order for them to appreciate working with coworkers who support one another in completing tasks and who exhibit high levels of work motivation.